The effect of chord duration on the relative salience of chord-type and voicing changes - Jimenez, Ivan; Kuusi, Tuire; Ojala, Juha; Harrison, Peter (Sage, 2024)
This study investigates the effect of chord duration on the relative salience of chord-type and voicing changes. Participants (N = 111) with varying levels of musical training were presented with sequences of five block chords on the piano and asked to indicate which chord sounded most different. Each sequence consisted of three identical chords and two oddballs, one with a voicing change and one with a chord-type change. All possible chord-type pairings between standard and oddball formed of major, minor, dominant seventh, major seventh, and minor seventh chords were tested. In addition, each sequence of five chords was tested using three chord duration conditions (500, 1,000, and 1,500 ms), and the durations were pseudo-randomized throughout the experiment. Chord-type changes became more salient with longer durations and this effect could be seen for all participants regardless of their levels of musical training. However, with higher level of musical training, chord-type changes became more salient across all duration conditions. Leman’s model of tonal contextuality suggests that the effect of duration in our experiment could be explained by sensory mechanisms related to echoic memory. The potential contribution of other factors to the effect of duration is discussed.
Keywords: soinnutus; sointuoppi; musiikinteoria; tonaalisuus